Watery Eyes, Drifting Images: Visual Ecocriticism, Photographic Archives and the Muddy History of the Maputo Bay, Southern Mozambique - Caio Simões De Araújo (Kronos)
The flourishing field of environmental humanities has increasingly called for a shift in perspective, urging scholars to de-centre the human and engage deeply with the materialities of both organic and inorganic matter. This approach requires broadening our understanding of historical agency and perception, recognising the roles of randomness, matter, climate, weather, and non-human forces in shaping historical narratives. Moreover, environmental histories challenge us to reimagine the archive, moving beyond the nation-state's authority as the primary custodian of historical knowledge. In this article, I explore these by bringing an ecocritical lens to the practice of visual history, focusing on the shoreline of southern Mozambique. I engage with the materiality of the shore - its multiple temporalities, fractal nature, and amphibian quality as a space that is neither fully terrestrial nor oceanic. Thinking with the shoreline, I argue, compels us to take its materialities seriously as a dynamic contact zone between soil and water. But how can we construct such a 'muddy' history? This article draws on three sets of images to address this question: colonial photographs of weather events such as cyclones and floods in Lourenço Marques; underwater images of marine hunting and wildlife, a popular activity during the late colonial period; and personal photographs of gay men at the beach, which reimagine the coast as a queer space. Together, these images invite us to reconceptualize the (visual) history of Maputo Bay, moving beyond conventional narratives to embrace a fluid, archival imagination - one that sees with watery eyes and drifts with the images themselves.